2010
DOI: 10.1016/j.jvs.2009.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of ruptured thoracic aortic aneurysms is associated with high perioperative mortality and morbidity

Abstract: The endovascular treatment of ruptured thoracic aortic aneurysms is associated with a high perioperative mortality and morbidity as well as poor midterm survival. Renal insufficiency proved to be an independent risk factor for perioperative death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…The incidence of respiratory complications after TEVAR for thoracic aortic rupture has been reported in the range of 15e 39%. 2,4,5,22,25 A recent nationwide study on use and outcomes of TEVAR for ruptured thoracic aortic aneurysms reported that respiratory complications were alarmingly high at 63%, and even higher in the TEVAR group compared with conventional repair. 3 However, when pleural effusion or HTX were eliminated from the final analysis the respiratory complications were lower in the TEVAR group.…”
Section: Population Based Analysis and Single Center Studies Have Repmentioning
confidence: 99%
“…The incidence of respiratory complications after TEVAR for thoracic aortic rupture has been reported in the range of 15e 39%. 2,4,5,22,25 A recent nationwide study on use and outcomes of TEVAR for ruptured thoracic aortic aneurysms reported that respiratory complications were alarmingly high at 63%, and even higher in the TEVAR group compared with conventional repair. 3 However, when pleural effusion or HTX were eliminated from the final analysis the respiratory complications were lower in the TEVAR group.…”
Section: Population Based Analysis and Single Center Studies Have Repmentioning
confidence: 99%
“…Despite an initial successful TEVAR, the main drawback is the development of procedure‐related complications that need additional secondary endovascular or conventional surgical interventions . There is a 4.5–16% reported incidence of late secondary interventions based on a very heterogenic follow‐up duration . In our series, two patients underwent early secondary interventions (a second TEVAR within one week of the first session) and six patients had major late complications that required a total of seven secondary interventions.…”
Section: Discussionmentioning
confidence: 81%
“…TEVAR has emerged as an alternative to open surgery for acute rupture of different aortic pathologies . Currently, there is little experience regarding emergency TEVAR for patients with nontraumatic rupture of the descending thoracic aorta and their follow‐up duration is limited …”
mentioning
confidence: 99%
“…21 Yet this has not precluded the use of TEVAR for patients with ruptured aneurysms, as evidenced by reports from multiple centers. This trend reflects the commencement of a paradigm shift in the approach to treating this formidable surgical challenge.…”
Section: Article See P 2718mentioning
confidence: 99%